Extracellular Calcium-Sensing Receptor Inhibition of Intestinal EpithelialTNF Signaling Requires CaSR-Mediated Wnt5a/Ror2 Interaction - Kelly, Jacqueline; Lungchukiet, Panida; MacLeod, R.John (Frontiers in Physiology, 2011)
Tumor necrosis factor (TNFα) and its receptor TNFR1 play a central role in the development of colitis associated colon cancer. To understand a role for the extracellular calcium-sensing receptor (CaSR) and its noncanonical Wnt mediators, Wnt5a/Ror2, we used reductionistic systems. We added lipopolysaccharide (LPS) to mouse peritoneal macrophages, RAW264.7 cells, a murine macrophage cell line and 18Co colonic myofibroblasts, to stimulate TNFα secretion and then activated endogenous CaSR. CaSR activation inhibited TNFα secretion, which in RAW264.7 cells knockdown of CaSR by siRNA duplex reversed. LPS-stimulated NFκB promoter activity in RAW264.7 cells was inhibited by CaSR activation with Ca2+ or other polyvalent CaSR agonists. Reducing CaSR expression with siRNA duplex prevented this inhibition. Following LPS addition to CaSR-HEK cells or RAW264.7 macrophages, CaSR stimulation deneddylated Cullin1. Wnt5a added to HT-29 cells which overexpressed Ror2 or T84 monolayers treated with 3 mM Ca2+ reduced TNFR1 protein expression 70%. TNFα/INFγ addition to high resistance T84 monolayers reduced transepithelial resistance 50% within 4h. CaSR activation (3 mM Ca2+) together with rhWnt5a (200ng/ml) prevented this reduction while Wnt3a addition had no effect. LPS-stimulated TNFα secretion from RAW 264.7 cells was not effected by rhWnt5a but increased 10 fold by Wnt3a. Together our results suggest that following LPS challenge, CaSR activation will inhibit NFκB activity and reduce TNFα secretion from macrophages and stroma while Wnt5a/Ror2 engagement on intestinal epithelia reduces TNFR1 expression, allowing TNFα signaling to be titrated. Our results also suggest that canonical Wnt signaling may enhance TLR4 stimulation of TNFα secretion from murine macrophages.